Термічне та хімічне модифікування природних морденітів як метод отримання нових цеолітних матеріалів - Tsintskaladze, G. P.; Eprikashvili, L. G.; Kordzakhia, T. N.; Nanikashvili, P. M.; Sharashenidze, T. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
By method of IR-spectroscopy, termo- and acid- resistences of natural mordenites of various deposits have been studied. It is shown, that the materials obtained as a result of thermal and chemical processing of mordenite are characterized by high termo- and acid- resistency. Studying of IR-spectra of the initial and hydrogen forms of mordenite in the range of deformation and valence fluctuations of water molecules (1600-3700 sm-1) has been shown, that the obtained hydrogen forms of natural mordenite are characterized by high concentration of the active centers and termo- . Thus, new nano-porous materials, which can be used in a number of technological processes, are possible to be obtained from mordenite.